2005
DOI: 10.1097/00124784-200511001-00006
|View full text |Cite
|
Sign up to set email alerts
|

Applying Risk Perception Theory to Public Health Workforce Preparedness Training

Abstract: Since 9/11, public health has seen a progressive culture change toward a 24/7 emergency response organizational model. This transition entails new expectations for public health workers, including (1) a readiness and willingness to report to duty in emergencies and (2) an ability to effectively communicate risk to an anxious public about terrorism or naturally occurring disasters. To date, however, research on readiness education for health department workers has focused little attention upon the risk percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 12 publications
4
39
0
2
Order By: Relevance
“…The JH-PHIRST instrument also contains a series of other relevant attitude/belief statements derived from an initial pilot survey in Maryland conducted in 2005 by study team members (Balicer et al, 2006). The instrument was based on validated risk communication theory (Slovic et al, 1985;Sandman et al, 1993) in the context of an identified set of potential risk perception modifiers from emergency preparedness training experiences in LHDs (Barnett et al, 2005). The JH-PHIRST assessment allowed LHD staff to respond to constructs representing attitude/belief statements under four different public health scenarios, including a weather-related disaster, a pandemic influenza emergency, a radiological ("dirty") bomb emergency, and an inhalational anthrax bioterrorism emergency.…”
Section: Survey Instrumentmentioning
confidence: 99%
See 2 more Smart Citations
“…The JH-PHIRST instrument also contains a series of other relevant attitude/belief statements derived from an initial pilot survey in Maryland conducted in 2005 by study team members (Balicer et al, 2006). The instrument was based on validated risk communication theory (Slovic et al, 1985;Sandman et al, 1993) in the context of an identified set of potential risk perception modifiers from emergency preparedness training experiences in LHDs (Barnett et al, 2005). The JH-PHIRST assessment allowed LHD staff to respond to constructs representing attitude/belief statements under four different public health scenarios, including a weather-related disaster, a pandemic influenza emergency, a radiological ("dirty") bomb emergency, and an inhalational anthrax bioterrorism emergency.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…WTR is associated with how emergency events are perceived (e.g., familiarity and severity of the threat), expectations about the role one will play (e.g., response efficacy and self-efficacy), and the personal and family impact an event is anticipated to have (e.g., severity, susceptibility, and self-efficacy to deal with the threat) (Barnett et al, 2009). Consistent with risk perception theory (Burns et al, 2012;Slovic et al, 1985;Slovic et al, 2004), preparedness training requires careful attention to how responders perceive risks and the sense of dread they attach to risks, especially when they are infrequent or novel (Barnett et al, 2005). Downloaded by [York University Libraries] at 06:05 17 November 2014…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Radiology nurses may be uniquely positioned to bring their expertise to a large-scale radiation event in planning, preparedness, and response. Willingness to respond to disaster events involving radiation may be dependent on the nurses' perception of risk (Barnett et al, 2005) and sense of clinical competence (Mitani, Kuboyama, & Shirakawa, 2003;Mitchell, Kernohan, & Higginson, 2012;Veenema, Walden, Feinstein, & Williams, 2008). Despite this knowledge, insufficient attention and resources continue to be allocated in the United States to the education and training of nurses and other health care providers in the medical institutions that will receive victims (Dallas, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…10 It has been previously suggested that contributing factors peripheral to the actual risk will have a considerable impact on how employees will respond in a crisis. 10 Apart from physical and circumstantial barriers such as the dependence of family members, other risk perception issues that could impact on HCWs' ability to respond may include the manageability of the threat, direct personal impact, and their sense of control over the events. 11 In light of the current situation, health departments must optimize the response rate of their employees in this crisis scenario.…”
Section: Introductionmentioning
confidence: 99%